Immune deficiency is a risk factor for severe COVID‐19 in people living with HIV. Issue 5 (27th December 2020) - Hoffmann, Christian; Casado, José L.; Härter, Georg; Vizcarra, Pilar; Moreno, Ana; Cattaneo, Dario; Meraviglia, Paola; Spinner, Christoph D.; Schabaz, Farhad; Grunwald, Stephan; Gervasoni, Cristina
Abstract : Objectives: A prior T cell depletion induced by HIV infection may carry deleterious consequences in the current COVID‐19 pandemic. Clinical data on patients co‐infected with HIV and SARS‐CoV‐2 are still scarce. Methods: This multicentre cohort study evaluated risk factors for morbidity and mortality of COVID‐19 in people living with HIV (PLWH), infected with SARS‐CoV‐2 in three countries in different clinical settings. COVID‐19 was clinically classified as to be mild‐to‐moderate or severe. Results: Of 175 patients, 49 (28%) had severe COVID‐19 and 7 (4%) patients died. Almost all patients were on antiretroviral therapy (ART) and in 94%, HIV RNA was below 50 copies/mL prior to COVID‐19 diagnosis. In the univariate analysis, an age 50 years or older, a CD4+ T cell nadir of < 200/µl, current CD4+ T cells < 350/µl and the presence of at least one comorbidity were significantly associated with severity of COVID‐19. No significant association was found for gender, ethnicity, obesity, a detectable HIV RNA, a prior AIDS‐defining illness, or tenofovir (which was mainly given as alafenamide) or protease inhibitor use in the current ART. In a multivariate analysis, the only factor associated with risk for severe COVID‐19 was a current CD4+ T cell count of < 350/µl (adjusted odds ratio 2.85, 95% confidence interval 1.26‐6.44, p=0.01). The only factor associated with mortality was a low CD4 T cell nadir. Conclusions: In PLWH, immune deficiency is a possible risk factor for severe COVID‐19, even in the setting of virological suppression. There is no evidence for a protective effect of PIs or tenofovir alafenamide.